Plasticity in Multiple Sclerosis: From Molecular to System Level, from Adaptation to Maladaptation - Daniel Zeller (Frontiers Research Topics, 2016)
This research topic aims at providing a state of the art update on neuroplasticity in humans with multiple sclerosis. It summarizes advances in plasticity research as achieved by a variety of techniques, in the motor as well as visual and cognitive domain. We are confident that this collection of articles broadens the view across systems and techniques and widens our understanding of this exciting field of research.